2015
DOI: 10.1080/10926771.2015.1002653
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Parenting in Relational Aggression and Prosocial Behavior among Emerging Adults

Abstract: This study investigated the role of remembered parenting styles and parental psychological control in the prediction of relational aggression and prosocial behavior in a college student sample ( N = 323). Participants' retrospective ratings of how they were parented were related to relational aggression and prosocial behavior; however, somewhat different relationships emerged for African American and White participants. Permissive parenting, authoritative parenting, and parental psychological control predicted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 61 publications
1
33
0
2
Order By: Relevance
“…Cronbach’s alpha reliabilities from age 13 to age 18 ranged from α = .90 to α = .93 for the total sample, from α = .88 to α = .92 for boys, and from α = .90 to α = .94 for girls. In addition to high internal consistency, previous research revealed high convergent validity for this measure (Hawk et al 2013 ; Clark et al 2015 ).…”
Section: Methodsmentioning
confidence: 72%
“…Cronbach’s alpha reliabilities from age 13 to age 18 ranged from α = .90 to α = .93 for the total sample, from α = .88 to α = .92 for boys, and from α = .90 to α = .94 for girls. In addition to high internal consistency, previous research revealed high convergent validity for this measure (Hawk et al 2013 ; Clark et al 2015 ).…”
Section: Methodsmentioning
confidence: 72%
“…In the current study, Cronbach's alphas ranged across waves from .87 to .92. In addition to high internal consistency, previous research revealed high convergent validity for this measure of prosociality, showing that it was positively related to perspective taking and empathic concern (Hawk et al, ) and negatively related to relational aggression (Clark, Dahlen, & Nicholson, ). Importantly, the magnitude of these associations was generally moderate, indicating that prosociality was distinct from empathy and relational aggression.…”
Section: Methodsmentioning
confidence: 81%
“…Therefore, parental psychological control during adolescence can be considered as stressful parenting, which could affect the social development of adolescents. Indeed, parental psychological control has been related to lower levels of social behavior and higher levels of relational aggression in adolescents (Loukas et al 2005 ) and emerging adults (Clark et al 2015 ).…”
Section: Introductionmentioning
confidence: 99%